Work-Family Conflict, Social Support, and Anxiety in Adults - Amjad, Saira; Khan, Muhammad Luqman; Khan, Saira (Annals of Human and Social Sciences, 2025)
The present study examined the relationship between work, family conflict, social support and anxiety in adults .After detailed review of literature following hypothesis are formulated. There will significant relationship between work family conflict, social support and anxiety level in adults. The total number of sample was 294 from individuals who are employed whose age falls between 18 and 35 years. Demographic sheet were used to get the personal information about the participant. Work and family conflict scale was used to measure work family conflicts. The Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure the social support. The Zung Self-Rating Anxiety Scale (SAS) was used to measure the anxiety in adults. The study found that work-family conflict increases anxiety, but strong social support helps reduce this effect. Social support has a moderating effect on the relationship between work-family conflict and anxiety.